Nocardia Keratitis following penetrating corneal injury treated with topical ampicillin - Bhusal, Bijay; Kumar, A; Prajna, N V; Srinivasan, M (Nepalese Journal of Ophthalmology, 2016)
Background: Nocardia keratitis following surgical management of penetrating corneal injury is very rare. Case: A 38-year-old male presented with a deep stromal corneal infiltration with hypopyon of 10 days duration in his left eye. He had undergone a corneal tear repair on that eye 15 days prior to the onset of keratitis. The infiltrations were along the sutured corneal tear tracts. Before presenting to us, he was treated empirically with hourly topical antifungal and antibiotic for 10 days with poor clinical response. Microbiological investigations revealed the presence of Nocardia in both smear and culture. The infiltrations responded well to fortified 5% ampicillin eye drops. Conclusion: Although Nocardia keratitis is very rare following penetrating corneal injuries and clinically can mimic mycotic keratitis, it should also be suspected in cases not responding to standard treatment. Management of Nocardia keratitis requires a good clinical judgement with appropriate microbiological support. Nepal J Ophthalmol 2016; 8(15): 82-86